Thelypteris indusiata (Thelypteridaceae), a new fern species from Amazonian Brazil - Salino, Alexandre; de Souza, Maria Gabriela Marques; Arruda, André Jardim (Phytotaxa, 2014)
Thelypteris indusiata is described as a new species from Amazonian Brazil. This species with 1-pinnate laminae and terminal pinnae that resemble lateral ones belongs to Thelypteris subgenus Goniopteris and resembles several other species, mainly T. poiteana, T. ghiesbreghtii, T. vivipara and T. platypes, but differs from these species mainly by the venation pattern and the indusiate sori.